Policy Output Analysis Pada Pencegahan Kekerasan Anak Dalam Keluarga Melalui Layanan Puspaga Di Surabaya - Hafzari, Alvina Dewi (Universitas Muhammadiyah Mataram, 2023)
Violence against children is a serious social problem, and the number of cases of violence against children changes every year. Cases of violence against children often occur in families, so the prevention of violence against children in families must be encouraged by everyone, including the government. The Surabaya City Government has made various efforts to prevent child violence in the family, one of which is through PUSPAGA. PUSPAGA Kota Surabaya is a service under the auspices of the DP3APPKB Surabaya City which focuses on strengthening families and preventing violence against children. This study uses a qualitative descriptive approach. The theory used is the theory of policy output evaluation with 7 (seven) indicators of Ripley's policy output, namely access, frequency, coverage, bias, service delivery (accuracy of service), accountability, and suitability of programs with needs. PUSPAGA Surabaya City has provided good service on each indicator. Even so, the Surabaya City Government still has to continue to introduce it to the public so they know more about PUSPAGA services in Surabaya City.